Increased susceptibility to drought‐induced mortality in Sequoia sempervirens (Cupressaceae) trees under Cenozoic atmospheric carbon dioxide starvation1. Issue 3 (1st March 2013) - Quirk, Joe; McDowell, Nate G.; Leake, Jonathan R.; Hudson, Patrick J.; Beerling, David J.
Abstract : Premise of the study: Climate‐induced forest retreat has profound ecological and biogeochemical impacts, but the physiological mechanisms underlying past tree mortality are poorly understood, limiting prediction of vegetation shifts with climate variation. Climate, drought, fire, and grazing represent agents of tree mortality during the late Cenozoic, but the interaction between drought and declining atmospheric carbon dioxide ([CO2 ]a ) from high to near‐starvation levels ∼34 million years (Ma) ago has been overlooked. Here, this interaction frames our investigation of sapling mortality through the interdependence of hydraulic function, carbon limitation, and defense metabolism. Methods: We recreated a changing Cenozoic [CO2 ]a regime by growing Sequoia sempervirens trees within climate‐controlled growth chambers at 1500, 500, or 200 ppm [CO2 ]a, capturing the decline toward minimum concentrations from 34 Ma. After 7 months, we imposed drought conditions and measured key physiological components linking carbon utilization, hydraulics, and defense metabolism as hypothesized interdependent mechanisms of tree mortality. Key results: Catastrophic failure of hydraulic conductivity, carbohydrate starvation, and tree death occurred at 200 ppm, but not 500 or 1500 ppm [CO2 ]a . Furthermore, declining [CO2 ]a reduced investment in carbon‐rich foliar defense compounds that would diminish resistance to biotic attack, likely exacerbating mortality. Conclusions: Low‐[CO2 ]a ‐driven tree mortality under drought is consistent with Pleistocene pollen records charting repeated Californian Sequoia forest contraction during glacial periods (180–200 ppm [CO2 ]a ) and may even have contributed to forest retreat as grasslands expanded on multiple continents under low [CO2 ]a over the past 10 Ma. In this way, geologic intervals of low [CO2 ]a coupled with drought could impose a demographic bottleneck in tree recruitment, driving vegetation shifts through forest mortality.